Chronology of thripsological activities and comparison of check-lists on Thysanoptera in Slovenia and FR Yugoslavia - Trdan, Stanislav (Acta entomologica slovenica (Ljubljana), 2003)
A chronology of thripsological activities in Slovenia and FR Yugoslavia is presented. A check-list of thrips (Thysanoptera), so far recorded in both countries, includes 149 species, 107 (78 species of suborder Terebrantia and 29 species of suborder Tubulifera) in Slovenia and 114 (74 species of suborderTerebrantia and 40 species of suborder Tubulifera) in FR Yugoslavia. Among the most important collectors of thrips are zur Strassen and Janežič forSlovenia and Andjus and Kazakov for Yugoslavia.
Keywords: entomologija; resarji; Slovenia; Slovenija